Zoom: Powerful women - Katerina Markelova (The UNESCO Courier, 2020)
Naliapou, the doyenne of Tumai, a Kenyan village forbidden to men, prepares for a chanting ceremony to the spirits, by coating her face with red earth mixed with animal fat.